1999
DOI: 10.1007/s004360050620
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected increased thiabendazole tolerance in Haemonchus contortus resistant to anthelmintics by modulation of glutathione activity

Abstract: The effect of several modulators of the synthesis or activity of glutathione (GSH) on the susceptibility of Haemonchus contortus eggs susceptible or resistant to anthelmintics was investigated using in vitro egg-hatch assays. Diethylmaleate, D,L-buthionine-[S,R]-sulfoximine, and patulin induced an unexpected decrease in the susceptibility of resistant eggs to thiabendazole, which was chosen as a reference for resistance to benzimidazole compounds. The results demonstrate that the level of GSH or SH analog play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In addition, somatic extracts of cestode and digenean parasites have higher activity towards lipid peroxidation products than nematodes, including H. contortus, do (2, 9). Parasite GSTs have also been associated with drug resistance (18,19). HcGST-1, isolated from a drug-resistant strain of H. contortus, only weakly bound the majority of commercial anthelmintics, with no evidence of enzymatic conjugation (results not shown).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, somatic extracts of cestode and digenean parasites have higher activity towards lipid peroxidation products than nematodes, including H. contortus, do (2, 9). Parasite GSTs have also been associated with drug resistance (18,19). HcGST-1, isolated from a drug-resistant strain of H. contortus, only weakly bound the majority of commercial anthelmintics, with no evidence of enzymatic conjugation (results not shown).…”
Section: Resultsmentioning
confidence: 97%
“…The levels of the phase II detoxification system glutathione transferase (GST) have been shown to increase in parasitic helminths during chronic infection (3). Previous research has attempted to correlate this overexpression with the ability of GST to detoxify immune-initiated cytotoxic products of lipid peroxidation (8, 10) or has associated the overexpression of GST, including H. contortus GST, with drug resistance (18,19). In this paper, we analyze a new GST from the sheep strongylid H. contortus and show that this GST does not appear to have a broad immune defense or drug metabolism role but possibly has a more focused detoxification function within the nematode.…”
mentioning
confidence: 99%
“…In F. hepatica, as many as eight GST isoforms have been shown to be present (Wijffels et al 1992). Altered GST activity has been linked to salicylanilide resistance in F. hepatica (Miller et al 1994), as well as thiabendazole resistance (Kerboeuf and Aycardi 1999) and cambendazole resistance (Kawalek et al 1984) in H. contortus.…”
Section: Introductionmentioning
confidence: 98%
“…The data suggested that increased TBZ tolerance may depend on different associated or unassociated factors. These included the ability of TBZ to conjugate with parasitic GSH or analogs, the potential toxicity of such conjugates, their cellular distribution, and their role in glutathione S-transferase [48].…”
Section: Detoxification Processesmentioning
confidence: 99%
“…The very strong functional involvement of Pgp in transporting anthelmintics was recently demonstrated in in vitro assays of living stages of H. contortus. Thus, the role of Pgp in the anthelmintic resistance of these invertebrates is now obvious [8,48,[54][55][56]95] …”
Section: Xenobiotic Transport By Pgpmentioning
confidence: 99%